(untitled) (Proceedings OPTIMAL, 2026)
Purpose: This study aimed to examine the effectiveness of a rhizome-based herbal drink combined with lime in reducing gout-related pain among elderly individuals. Methodology: This study employed a quantitative approach using a quasi-experimental design with a nonequivalent control group. A total of 20 elderly participants with chronic gout pain were selected through purposive sampling and divided into an intervention group (n = 10) and a control group (n = 10). Pain intensity was measured using the Numeric Rating Scale (0–10) before and after the intervention. Data were analyzed using descriptive statistics and the Wilcoxon Signed Rank Test with a significance level of p < 0.05. Findings: The results showed a significant reduction in pain scores in the intervention group, from 6.80 ± 0.79 to 3.80 ± 1.14 (p = 0.004). The control group also showed a reduction, from 6.50 ± 0.71 to 5.20 ± 1.32 (p = 0.009), but the magnitude of pain reduction was greater in the intervention group. Practical/Social Implications: These findings indicate that rhizome herbal drinks with lime can be applied as a safe, affordable, and easily implemented non-pharmacological therapy in community-based elderly care, particularly to reduce dependence on long-term pharmacological treatment. Originality/Value: This study provides empirical evidence on the effectiveness of a locally available herbal combination as a complementary therapy for gout-related pain among the elderly in a community setting, an area that remains underexplored in previous research.